Impact of Rapid Response Teams on Patient Outcomes in Emergency Departments: A Multicenter Study - Bishan Nandy (Journal of Pharmacy and Bioallied Sciences, 2025)
Objective: To evaluate the impact of rapid response teams (RRTs) on patient outcomes in emergency departments (EDs), including in-hospital mortality, unplanned ICU admissions, and length of stay (LOS), through a multicenter observational study. Methods: This prospective study was conducted across six tertiary hospitals, involving 2000 adult patients who met RRT activation criteria. Data from the time of RRT activation to discharge or death were analyzed using multivariate logistic regression models, adjusting for patient demographics, comorbidities, and severity of illness. Key outcomes included in-hospital mortality, ICU admissions, and LOS. Results: RRT intervention resulted in a 20% reduction in in-hospital mortality (adjusted OR 0.80, P = 0.03), a 15% reduction in unplanned ICU admissions (adjusted OR 0.85, P = 0.02), and a 1.5-day reduction in LOS (P < 0.05). Early RRT activation within one hour of symptom onset was associated with improved outcomes. Conclusion: The implementation of RRTs in EDs significantly improves patient outcomes, emphasizing the importance of early activation. These findings support the integration of RRTs into emergency care protocols to enhance patient survival and optimize resource utilization.